Biologically excretable AIE nanoparticles wear tumor cell-derived "exosome caps" for efficient NIR-II fluorescence imaging-guided photothermal therapy. (December 2021) - Li, Yirun; Fan, Xiaoxiao; Li, Yuanyuan; Zhu, Liang; Chen, Runze; Zhang, Yiyin; Ni, Huwei; Xia, Qiming; Feng, Zhe; Tang, Ben Zhong; Qian, Jun; Lin, Hui
Abstract: Nanoparticles (NPs) assisted photothermal therapy (PTT) is a promising cancer treatment modality and has attracted the attention of the scientific mainstream. However, developing bio-excretable NPs that exhibit efficient optical properties and specific tumor targeting capability simultaneously is difficult. Herein, we develop a kind of hybrid nanovesicles consisting of bio-excretable aggregation-induced emission (AIE) NPs and tumor cell-derived "exosome caps" (TT3- o CB NP@EXOs) with enhanced second near-infrared (NIR-II, 900–1700 nm) fluorescence property and PTT functionality via electroporation. Compared with TT3- o CB NPs, TT3- o CB NP@EXOs exhibit excellent biocompatibility, specific targeting ability in vitro, homing to homologous tumors in vivo, and prolonged circulation time. Furthermore, TT3- o CB NP@EXOs were utilized as biomimetic NPs for NIR-II fluorescence imaging-guided PTT of tumors, due to their high and stable photothermal conversion capacity under 808 nm irradiation. Therefore, with the validation of other AIE NPs with poor targeting property, the tumor cell-derived EXO/AIE NP hybrid nanovesicles may provide an alternative artificial targeting strategy for improving tumor diagnosis and PTT. Graphical Abstract: ga1 Highlights: A novel model of encapsulation "exosome caps" which produced via electroporation is proposed. "Exosome caps" improve the tumor targeting capability of AIE NPs and facilitate the NIR-II fluorescence imaging-guided PTT. Systematic study on the reasons why exosomes enhance the accumulation of AIE NPs in tumor via NIR-II fluorescence imaging.